Stagflationary Stock Returns - Ben Knox; Yannick Timmer (CESifo GmbH, 2024)
We study investors' perceptions of inflation through the lens of a high-frequency event study and document that they have a stagflationary view of the world. In response to higher-than-expected inflation, investors expect firms' nominal cash flows to remain stagnant while discount rates increase, resulting in lower stock prices. Both the equity risk premium and nominal risk-free yields rise. However, longer-term real yields remain unchanged, and policy-sensitive real yields even decline, with increases in nominal yields offset by larger increases in inflation expectations. Consistent with a stagflationary view in which investors interpret inflation as a marginal cost shock, investors expect firms with low market power to suffer larger declines in cash flows. Cash flow expectations of equity investors are aligned with those of professional earnings analysts, both in the time series and across the market power distribution.
Keywords: G12; E31; E44; L11; 330; inflation; stock returns; stagnant cash flows; market power